Algorithms as medical devices - Hall, Alison, Johan Ordish; Richardson (nee Murfet), Hannah (PHG Foundation, 2019)
From wearables for health monitoring and self-care apps, to machine learning analysis of medical images, the potential of digital technologies to revolutionise healthcare has commanded many headlines. Realising the medical benefits of such technologies needs appropriate regulation. In reality, identifying where a device fits within the complex and evolving regulatory environment is far from simple. The rapid growth of digital devices, software and technologies means that the medical device sector is changing. Many small and independent manufacturers are encountering medical device regulation for the first time. At the same time, responsive and effective regulation of digital devices requires sound understanding of the underlying new technologies and concepts. Algorithms as medical devices describes how digital health is covered by existing medical device regulation and outlines three critical areas: The challenges that the digital health sector may pose for regulators and developers How digital devices can be regulated as medical devices under UK/EU and US law The specific problems that machine learning could pose to medical device regulation A resource for regulators and policy makers, this report makes recommendations for improving the regulation of digital medical devices.